A comprehensive transcriptome based meta-analysis to unveil the aggression nexus of oral squamous cell carcinoma - Soujanya J. Vastrad; Ganesan Rajalekshmi Saraswathy; Jagadish B. Dasari; Gouri Nair; Ashok Madarakhandi; Dominic Augustine; S.V. Sowmya (Biochemistry and Biophysics Reports)
Lymph node metastasis in oral cancer (OC) complicates management due to its aggressive nature and high risk of recurrence, underscoring the need for biomarkers for early detection and targeted therapies. However, the drivers of this aggressive phenotype remain unclear due to the variability in gene expression patterns. To address this, an integrative meta-analysis of six publicly available transcriptomic profiles, categorized by lymph nodal status, is conducted. Key determinants of disease progression are identified through functional characterization and the TopConfects ranking approach of nodal associated differentially expressed genes (DEGs). To explore the critical nexus between lymph node metastasis and OC recurrence, significant metastatic genes were cross-analysed with literature-derived genes exhibiting aberrant methylation patterns in OC recurrence. Their clinical relevance and expression patterns were then validated in an external dataset from the TCGA head and neck cancer cohort. The analysis identified elevated expression of genes involved in extracellular matrix remodelling and immune response, while the expression of genes related to cellular differentiation and barrier functions was reduced, driving the transition to nodal positivity. The highest-ranked gene, MMP1, showed a log-fold change (LFC) of 4.946 (95 % CI: 3.71, 6.18) in nodal-negative samples, which increased to 5.899 (95 % CI: 4.80, 6.99) in nodal-positive samples, indicating consistent elevation across disease stages. In contrast, TMPRSS11B was significantly downregulated, with an LFC of −5.512 (95 % CI: −6.63, −4.38) in nodal-negative samples and −5.898 (95 % CI: −7.15, −4.64) in nodal-positive samples. Furthermore, MEIS1, down-regulated in nodal-positive status, was found to exhibit hypermethylation at CpG sites associated with OC recurrence. This study represents the first transcriptomic meta-analysis to explore the intersection of lymph node metastasis and OC recurrence, identifying MEIS1 as a potential key contributor. These comprehensive insights into disease trajectories offer potential biomarkers and therapeutic targets for future treatment strategies.